PENGARUH KOMUNIKASI ANTAR DEPARTEMEN TERHADAP KINERJA KARYAWAN DI THE BISTROT RESTAURANT - Bayu Fajar Satyra (Majalah Ilmiah Widyacakra, 2019)
The purpose of this study was to determine and analyze the influence of inter-departmental communication on employee performance. The study was conducted by distributing questionnaires to 42 employees. Data analysis used included, validity test, reliability test, normality test, heteroscedasticity test, simple linear regression test, t test, and test coefficient of determination. Based on the results of the validity test there are 42 invalid questions and 33 valid questions. The invalid instrument is deleted because it is an outlier data. Based on the results of the reliability test shows that communication between departments has cronbach alpha of 0.699 while cronbach alpha on employee performance is 0.796. This shows that the instrument used is reliable. From the results of the normality test the value of Asymp Sig is 0.200 which means greater than 5% (0.05). This shows that the data used in this study is normally distributed. For the results of heteroscedasticity test, it was found that sig. independent variable 0.728 more than 0.05. It can be said that this shows no heteroscedasticity. From the results of a simple liner regression test shows a = 78,846 means that if there is no increase in communication between departments, then the employee performance constant value is 78,846, then b = 0,009 means if there is an increase in communication communication between departments of one unit, then the performance constant value employee amounting to 0.009. From the results of the t test show that the value of t count = 0.052 <t table 2.021, so that H0 is accepted and H1 is rejected. While the results of the coefficient of determination indicate that the Rsquare value is 0,000 or 0% which means there is no correlation between communication between departments with employee performance. It can be concluded that in the study there was no relationship between the influence of interdepartment communication on employee performance at The Bistrot Restaurant.